LEGAL AND ECONOMIC CONDITIONS FOR THE EU MEMBERSHIP - EXAMPLE OF THE REPUBLIC OF SERBIA - Dimovski, Darko T; Stanojević, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
The European Union (EU) is an important player at the international level, which has largely contributed to the smooth development of the world economy. Joining the European Union implies a fulfillment of various conditions. The authors focus on the example of the Republic of Serbia to analyze the legal and economic conditions that are requested for a membership in the European Union. In this regard, the legal conditions laid down in Chapter 23 were analyzed in the first part of the paper, through a review of the current status in the field of judiciary, fight against corruption and fundamental rights. Afterwards, the authors devoted a special attention to the study of some of the economic conditions that the Republic of Serbia must fulfill in the process of the European Union accession.